Yes. x = - 6. Here's how to show this:
Since 16 = 4^2, rewrite your eqn. as 4^(x - 6) = 4^(2 x).
The exponents of ' 4 ' must match! Then x - 6 = 2 x; so x = - 6.
CHECK: If x = - 6, x - 6 = -12, so 4^(x - 6) = 4^(-12) = 1(4^12)
= 1/16777216.
Meanwhile 16^(-6) = 1/(16^6) = 1/16777216.
So they're EQUAL. QED
Live long and prosper.
2007-04-27 13:27:23
·
answer #1
·
answered by Dr Spock 6
·
2⤊
0⤋
Take the base-4 logarithm of both sides:
|--: x-6 = 2x
|--: x = -6
Double-check the answer:
|--: 4^ ((-6)-6) ?=? 16^(-6)
|--: 4^(-12) = (4^2)^(-6) = 4^(2*(-6)): Yes.
2007-04-27 20:37:59
·
answer #2
·
answered by Joe S 3
·
0⤊
0⤋
4 = 2^2
16 = 2^4
(2^2)^(x - 6) = (2^4)^x
when you have an exponent to an exponent, you multiply the exponents
2 ^ (2x - 12) = 2^(4x)
since they have the same base, the exponent must be equal to each other
2x - 12 = 4x
-12 = 2x
x = -6
2007-04-27 20:29:34
·
answer #3
·
answered by 7
·
3⤊
0⤋
if you are looking for X and if this is ALGEBRA then i think im right..
i do believe the answer is -2...
solution:
4^(x-6) = 16^x
4x-24 = 16x
-24 = 16x - 4x
-24 = 12x
*to have only the x we need to eliminate the 12.. divide both sides by 12..
answer:
-2 = x
checking:
4^(-2-6) = 16^-2
4^-4 = 256
256 = 256
*equal, so my answer is correct! ;]
2007-04-27 20:31:20
·
answer #4
·
answered by ella C 1
·
0⤊
2⤋
4^(x-6) = 4^x/4^6
16^x = 4^2x
4^x = 4^6*4^2x
1 = (4^6)*(4^x)
take log of both sides
0 = 6*log(4) + x*log(4)
x = -6
2007-04-27 20:34:09
·
answer #5
·
answered by gp4rts 7
·
0⤊
0⤋
it's x= 22. it's very simple.
2007-04-27 20:32:05
·
answer #6
·
answered by Beautiful Dreamer 2
·
0⤊
2⤋
65536=x
2007-04-27 21:51:01
·
answer #7
·
answered by justin d 1
·
0⤊
0⤋